Integration of Key Building Blocks for Search and Rescue Robots (Serabot) - AUGUSTIN JOHN, ALVIN ANAND (Universiti Teknologi PETRONAS, 2016)
This paper aims to show techniques of integrating sub systems for search and rescue robot. Search and rescue robots requires interaction of several sub systems to accomplish its designated task. Sub systems used are inexpensive and energy efficient devices including raspberry pi 3, Arduino Mega, ultrasonic sensors, line sensors, motor drivers and 4 brush motors. The use of these sub systems provides a reliable and robust implementation of a robotic system. Raspberry Pi process instructions from the user by python programing. Meanwhile Arduino Mega uses standard c program to process instruction form the user. Raspberry pi serves as a backbone for image processing. The use of ultrasonic sensors is to detect obstacle and use of line sensor is to keep the robot inside the test field. Arduino acts as a central processing unit which process all the input from various sensors and raspberry pi to activate the actuators to enable robot movement and achieve task based on user’s instructions.